50 Common Native Plants Important In Florida's Ethnobotanical History - Ginger M. Allen; Michael D. Bond; Martin B. Main (EDIS)
In this document we provide an introduction to ethnobotany in Florida and brief insight into the historical importance of some of Florida's plants to humans. We hope this document inspires readers to further investigate their region's ethnobotanical history. This information is not intended as a guide to using plants for medicinal or other purposes. This document is Circular 1439, one of a series of the Wildlife Ecology and Conservation Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: December 2002.